Improving Drama Listening Competence through the Direct ‎Listening Activity Model - Sri Suharyani; Umi Kulsum; Luthfi Permana Putra Setya (JPI: Jurnal Pustaka Indonesia, 2023)
This study aims to improve students’ competence in listening to drama within Indonesian language learning by applying the Direct Listening Activity (DLA) model. The research was designed as classroom action research involving 31 Grade XI students at SMKN 2 Bengkulu, conducted in two cycles, each consisting of planning, action, observation, and reflection. Data were collected through observation, tests, interviews, and documentation, and analyzed using data reduction, display, and verification supported by triangulation to ensure validity. The findings demonstrate that the application of the DLA model effectively enhanced student learning outcomes, with an average score increase of 7.81 points, mastery learning improving by 2.77%, and student participation rising by 8.34% from the first to the second cycle. Beyond cognitive gains, the DLA model also fostered students’ confidence, collaboration, and active engagement in appreciating drama. These results indicate that the DLA model is a practical pedagogical strategy for strengthening listening competence in Indonesian language education, with broader implications for fostering literary appreciation and communicative skills.